TRUST IN KNOWLEDGE TRANSFER PROCESS VIA ELECTRONIC BANKING WEB SITE - Zaid, Ali Abu; Azman, Norhidayah (Journal of Techno-Social, 2016)
As a result of the emergence of ICT in the last two decades, the number of Internet users has increased dramatically but most of them are reluctant to provide sensitive information to banking web sites because they do not trust e-banking web sites. In order that e-banking industry can go forward to sustainability, it requires growing trust, and decreases the opportunity of unlawful operations and is founded on knowledge transfer researches. This research has adapted knowledge transfer model as a means to study trust factor in more detail and depth. Also, this research evaluates trust and determines at which stage of knowledge transfer process is of concern in a Malaysian context. Results have shown that trust has a positive effect in all stages of knowledge transfer process, and that trust has a high correlation with initiation stage via electronic banking web sites in Malaysia. This research’s contribution is to help IT practitioners involved in developing web sites as successful channels for the delivery of bank knowledge resources to users.